Virtual Face to Face Meeting for Non-Technical Personnel - Santoso Budijono; Lukas Tanutama (Bina Nusantara University, 2020)
Covid-19 has impacted profoundly the business environment. Information and Communication Technology (ICT) becomes not only the major platform but also sustains the existence and running most business. Retail business becomes more dependent on technology. Small Business Enterprises (SME) have to jump and become savvy in ICT. The SME supply chain and marketing environment are moving toward ICT based platforms. On the other side the penetration of social media tool especially smartphone is widely spread. It can be safely assumed that every job holder whether entrepreneur, employee, or professionals or craftspeople is familiar with smartphones. The gap that must be bridged is using smartphone for business purposes. One of the business requirements that are not easy to replace is face to face communications. As Internet is ubiquitous and smartphones can easily access the Internet, there are numerous application that can resides both in computers and smartphones. The application that is closely similar to face to face meeting is known as Video Conference call. With this application it is possible to perform business briefing any time and anywhere provided there is Internet access. As business communication is not limited to technically savvy parties, a supportive system must be selected and introduced to them. We select Zoom as the application and develop a simple training syllabus. The syllabus has been implemented to a retail chain.